2008
DOI: 10.1111/j.1476-5381.2008.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Δ9‐tetrahydrocannabinol, a cannabinoid receptor agonist, on the triggering of transient lower oesophageal sphincter relaxations in dogs and humans

Abstract: Background and purpose: Transient lower oesophageal sphincter relaxations (TLESRs) are the main mechanism underlying gastro-oesophageal reflux and are a potential pharmacological treatment target. We evaluated the effect of the CB1/CB2 receptor agonist D -THC significantly reduced the number of TLESRs and caused a non-significant reduction of acid reflux episodes in the first postprandial hour. In addition, lower oesophageal sphincter pressure and swallowing were significantly reduced by D 9 -THC. After intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 33 publications
(40 reference statements)
2
56
0
2
Order By: Relevance
“…The effect of CBR1 agonists on the rate of TLOSRs has been studied in animal models 63,118,119 and humans. 119 It was found that CBR1 agonists reduce the rate of TLOSRs.…”
Section: Cbr1 Receptor Modulatorsmentioning
confidence: 99%
“…The effect of CBR1 agonists on the rate of TLOSRs has been studied in animal models 63,118,119 and humans. 119 It was found that CBR1 agonists reduce the rate of TLOSRs.…”
Section: Cbr1 Receptor Modulatorsmentioning
confidence: 99%
“…[30][31][32][33] Bu sonuçlarla doğrultulu olarak sağlıklı gönüllülerde yapılan çalışmada, ∆ 9 -THC'nin geçici LES relaksasyon sayısını azalttığı ve asit reflü ataklarında anlamlı olmayan bir azalma sağladığı gösterilmiştir. 32 Hepsi birden değerlendi-rildiğinde, CB reseptör aktivasyonunu sağlayan ilaç-ların gastroözofageal reflü tedavisinde umut verici bir yeri olduğu düşünülmektedir.…”
Section: Alt öZofageal Sfi̇nkter (Les) üZeri̇ne Etki̇leri̇unclassified
“…Ostatnio stwierdzono, że mieszany agonista receptorów CB1/CB2 redukuje występo-wanie indukowanych posiłkiem TLESR u zdrowych osób, ale podobnie jak baklofen wywiera działania ośrodkowe. Badanie zostało przerwane z powodu złej tolerancji: nudności, wymiotów, hipotensji, tachykardii i ośrodkowych objawów ubocznych [28].…”
Section: Agoniści Receptora Kannabinoidowegounclassified